Impact of one-dose package dispensing with patient counseling on medication adherence in geriatrics suffering from chronic disorders - Narayana Goruntla; Vijaya Jyothi Mallela; Devanna Nayakanti (Wolters Kluwer Medknow Publications, 2018)
Introduction: Medication nonadherence in elderly patients could result in a waste of medical expenses in a long-time span as well as deterioration of the patient's medical condition. Aim: The aim of this study is to evaluate the impact of one-dose package dispensing with patient counseling on medication adherence among elderly patients suffering from chronic disorders. Settings and Design: This is prospective, open-labeled, randomized trial carried out at dispensing pharmacy of the secondary care referral hospital, located in resource-limited settings of Anantapur District, Andhra Pradesh, India. Subjects and Methods: A total of 330 (aged ≥60 years) patients were randomly assigned to one of three study groups: Group A (n = 110), no change in dosing and packing; Group B (n = 110), one-dose package dispensing; Group C (n = 110), One-dose package dispensing with patient counseling. Medication adherence levels were measured using a pill count and visual analog scale (VAS) method at baseline and follow-up (after 1 month). Statistical Analysis: Descriptive statistics were used to represent the sociodemographic, clinical, and medication adherence profile of study participants. One-way ANOVA test is used to assess significant differences between three groups with a P < 0.05. Results and Discussion: Medication adherence levels measured by pill count and VAS method were significantly better in Group C (98.98 ± 1.34, 95.09 ± 5.02) one-dose package with patient counseling and Group B (92.93 ± 3.77, 90.09 ± 5.98) one-dose package dispensing than Group A (87.51 ± 6.23, 84.63 ± 6.86) conventional package (P = 0.0001, 0.004). Conclusion: Patients >60 years who are on multiple medications can benefit from one-dose package dispensing and appropriate counseling. This will improve medication adherence hence better outcomes.